The Occupy Movement vs. Capitalist Realism: Seeking Extraordinary Transformations in Consciousness - Fletcher, Samantha (2015)
In September 2011 the spreading sentiment of "Ya Basta!" ("Enough"), stemming from a combination of popular protests within the same decade, particularly those occurring in Spain as part of the Indignados movement (Castañedam 2012) and from the events commonly identified as the "Arab Spring", became apparent in the USA. The manifestation was a "scrappy group of anarchists" (Occupy Wall Street, 2014) who flooded into Liberty Square, New York, to start the movement that is now most commonly known as Occupy Wall Street. The initial call to action came from a blog from Adbusters Culture Jammers HQ by Justine Tunney and Micah White, two fo the "leaders" of the leaderless movement (Costanza-Chock, 2012). The piece called for a "Tahrir moment" (Adbusters, 2011) and reflected on the type of direct action and strategy that characterized previous anti/alter-globalization social movements. In October 2011 the UK soon followed suit with its own similar call to action on the steps of St Pauls Cathedral in London. Alongside the original inception of Occupy Wall Street, the style and name of Occupy spread globally, with action taking place in over 1,500 cities (Occupy Wall Street, 2014). Attempts to contextualize and understand the significance of what might be learnt from the happenings that took place in New York, and the broader global Occupy movement until it's largely physical, but by no means imaginative, demise at the hands of state actors, has continued to steadily emerge from critical criminology and associated critical disciplinary strands of thought